2021
DOI: 10.1177/0887302x21993500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiant Heat and Frictional Abrasion on Thermal Protective Performance of Clothing Against High Pressurized Steam

Abstract: This study focused on changes in protective performance of steam protective clothing after exposure to conditions such as thermal radiation and frictional abrasion. Totally eight radiation conditions varying on exposure duration and times, four types of abrasion scenarios with different friction cycles and three different combined treatments were designed. Results demonstrated that any increase in radiant exposure duration or exposure times would lead to an initial increase and then a following decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…They recommended that it is essential to place a moisture barrier with zero air permeability in the outer layer of multilayered fabric systems in order to achieve a high SPP. This air-impermeable moisture barrier will immediately stop the steam penetration through the fabric system, which will considerably decrease the chances of burns on the bodies of wearers [7,[18][19][20][21][22][23][24]. Along with air permeability, Desruelle et al (2002) indicated that the thickness of the fabric systems has a considerable impact on its steam protective performance [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They recommended that it is essential to place a moisture barrier with zero air permeability in the outer layer of multilayered fabric systems in order to achieve a high SPP. This air-impermeable moisture barrier will immediately stop the steam penetration through the fabric system, which will considerably decrease the chances of burns on the bodies of wearers [7,[18][19][20][21][22][23][24]. Along with air permeability, Desruelle et al (2002) indicated that the thickness of the fabric systems has a considerable impact on its steam protective performance [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous researchers extensively studied steam penetration through fabrics by evaluating the SPP, only a few studies focused considerably on the TTTE through fabrics in steam exposure of a certain duration [4][5][6][7][8][9][10][18][19][20][21][22][23][24][25][26]. This paper studied experimentally both the SPP and TTTE and identified fabric features affecting both.…”
Section: Introductionmentioning
confidence: 99%